Ways of Showing Love in Marriage – gender differences across generations and cultures - Huić, Aleksandra (Array, 2012)
How do husbands and wives show love to each other? Studies so far examined different behaviors tied to intensity of love, but we wondered whether individuals truly intend to express their love through such behaviors. Our goal was to ask spouses about ways of showing love directly. We developed a 40-item Ways of Showing Love Scale, which measures six broad categories: (1) communal and sacrificial behaviors, (2) physical affection, (3) verbal affection, (4) domestic instrumentality, (5) emotional openness and support, and (6) chivalry. Further on, we were interested in: (a) gender differences in the ways spouses report showing love ; (b) the stability of these differences across three generations of couples ; and (c) the role of culture in the ways husbands/wives report showing love. We gathered data from 302 Croatian and 456 Serbian married couples, who came from a wide range of education and employment backgrounds. In order to test for generational differences, couples were divided into three age brackets (20–35, 36–54, and 55–87 years). Lending support to the validity of our scale, spouses’ feelings of love predicted all six ways of showing love. Both husbands and wives reported expressing love through affection and by respecting each other’s needs. Whereas women indicated they show love by being open and supportive, as well as by doing housework, men indicated they show love through physical affection and acts of chivalry. Results seem to be stable across generations and cultures.